25-3g=88

Simple and best practice solution for 25-3g=88 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 25-3g=88 equation:


Simplifying
25 + -3g = 88

Solving
25 + -3g = 88

Solving for variable 'g'.

Move all terms containing g to the left, all other terms to the right.

Add '-25' to each side of the equation.
25 + -25 + -3g = 88 + -25

Combine like terms: 25 + -25 = 0
0 + -3g = 88 + -25
-3g = 88 + -25

Combine like terms: 88 + -25 = 63
-3g = 63

Divide each side by '-3'.
g = -21

Simplifying
g = -21

See similar equations:

| 6y-3x=14 | | 4x-kx=p | | (37x+61y)+(-3x+32y)= | | 3x^2-20x-16=0 | | 1.48g-5=0.18 | | 4.8=3700 | | 6r-7=2r+18 | | -16x^2+120x+400=300 | | 65+15p=35 | | (k-3)x^2-(3k-2)x+3k+1=0 | | 3(3.8+-0.6y)+y=9 | | .05=1.82/x | | -2y=4y-42 | | 64=-2(m+7)+m | | 63+7x=84+4x | | 4x-6x=12-20-5x | | 7x/2_x=0 | | 475+40+28h=601 | | 5x-3(4x-13)=81 | | 5(3.8+-0.6y)+3y=19 | | 16=4(v+1) | | 12n-9+2n-n=-87 | | 2w^2+6=-7w | | 5x-3(-5x-9)=127 | | 40=5ln(x-2)+6 | | 2w^2+6+7w=0 | | 7.95+4.35=60 | | -3x-6(3x+14)=147 | | -6x+4-3+x=11 | | 12-3=7(n-4)+5n | | (-14)(0.22)+(-16)(0.65)=(-18)(0.13) | | 8x+7y-3x= |

Equations solver categories